Understanding India’s Sustainable Land Management Research Landscape: Productivity, Collaboration, and Emerging Themes (2016–2025) - Muneer Ahmad; Undie Felicia Nkatv; Gorrety Maria Juma; Sajid Saleem (International Journal of Land, 2026)
Sustainable Land Management (SLM) has emerged as a critical research domain in India due to increasing land degradation, climate variability, population pressure, and competing land-use demands. Understanding the evolution, structure, and impact of scholarly research in this field is essential for guiding future research and policy interventions. This study presents a comprehensive scientometric assessment of India’s SLM research output during the period 2016–2025. Bibliographic data comprising 1,560 records were retrieved from the Web of Science Core Collection and analyzed using HistCite software to examine publication growth, authorship patterns, institutional contributions, source journals, document types, and international collaboration. Results reveal substantial and accelerating growth in SLM research, particularly after 2020, reflecting heightened policy relevance and interdisciplinary engagement. Journal articles dominate the literature, while review papers demonstrate disproportionately high citation impact, underscoring their role in knowledge synthesis. A small group of prolific authors and leading institutions, including IITs, agricultural research organizations, and major universities, contribute significantly to research productivity and influence. High-impact international journals play a central role in disseminating Indian SLM research globally. Collaboration analysis highlights strong research linkages with countries such as the United States, China, Australia, and the United Kingdom, enhancing citation visibility and scholarly impact. Overall, the study provides a structured overview of India’s SLM research landscape, identifies emerging trends and influential contributors, and offers evidence-based insights to support strategic research planning, interdisciplinary collaboration, and sustainable land-use policy development.
Keywords: Citation analysis; India; Research productivity; international collaboration; scientometrics; sustainable land management